Perturbation of the two-component signal transduction system, BprRS, results in attenuated virulence and motility defects in Burkholderia pseudomallei. (December 2016) - Lazar Adler, Natalie; Allwood, Elizabeth; Deveson Lucas, Deanna; Harrison, Paul; Watts, Stephen; Dimitropoulos, Alexandra; Treerat, Puthayalai; Alwis, Priyangi; Devenish, Rodney; Prescott, Mark; Govan, Brenda; Adler, Ben; et al.
Abstract Background Burkholderia pseudomallei is the causative agent of melioidosis, a severe invasive disease of humans and animals. Initial screening of aB. pseudomallei signature-tagged mutagenesis library identified an attenuated mutant with a transposon insertion in a gene encoding the sensor component of an uncharacterised two-component signal transduction system (TCSTS), which we designated BprRS. Results Single gene inactivation of either the response regulator gene (bprR ) or the sensor histidine kinase gene (bprS ) resulted in mutants with reduced swarming motility and reduced virulence in mice. However, abprRS double mutant was not attenuated for virulence and displayed wild-type levels of motility. The transcriptomes of thebprS, bprR andbprRS mutants were compared with the transcriptome of the parent strain K96243. Inactivation of the entire BprRS TCSTS (bprRS double mutant) resulted in altered expression of only nine genes, including bothbprR andbprS, five phage-related genes andbpss0686, encoding a putative 5, 10-methylene tetrahydromethanopterin reductase involved in one carbon metabolism. In contrast, the transcriptomes of each of thebprR andbprS single gene mutants revealed more than 70 differentially expressed genes common to both mutants, including regulatory genes and those required for flagella assembly and for the biosynthesis of the cytotoxic polyketide, malleilactone. Conclusions Inactivation of the entire BprRS TCSTS did not alter virulence or motility and very few genes were differentially expressed indicating that the definitive BprRS regulon is relatively small. However, loss of a single component, either the sensor histidine kinase BprS or its cognate response regulator BprR, resulted in significant transcriptomic and phenotypic differences from the wild-type strain. We hypothesize that the dramatically altered phenotypes of these single mutants are the result of cross-regulation with one or more other TCSTSs and concomitant dysregulation of other key regulatory genes.